Sistem Informasi Trouble Ticket (SIKET) Untuk Layanan Gangguan Jaringan Berbasis Web - Wijaya, Sapta Musta; Mustika, Wida Prima; Sanjaya, Andi (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Network service radio trunking PT.Handal Exa Teknologi often also gets various reports and complaints from users, currently users are still making reports and complaints using email and through group chat applications such as whats app , in the process of reporting this disturbance the helpdesk team is still doing manual recording. The purpose of this study is to create a web-based information system facility to process data on service interruption reports and be able to solve problems, can provide convenience for users to report service disruptions by using the website and maintain company service to users to be able to respond quickly in processing the handling of service disturbances, from the purpose of this research to produce a trouble ticket web-based ticket that can assist companies in data processing various reports and complaints of disturbances so that service to users becomes maximal and effective. The research method used in this study is based on qualitative methods. While the development of the system uses the waterfall model. The software used are: Windows Pro Home 10, Visual studio code, and Xampp.Information System Trouble Ticket -based Web at PT. Reliable Exa Technology that improves service to customers in terms of responding quickly to complaints that want to be reported and can be a medium for information on data disturbances that have occurred